Genome Wide Mapping of Peptidases in Rhodnius prolixus: Identification of Protease Gene Duplications, Horizontally Transferred Proteases and Analysis of Peptidase A1 Structures, with Considerations on Their Role in the Evolution of Hematophagy in Triatominae - Henriques, Bianca S.; Gomes, Bruno; Costa, Samara G. da; Moraes, Caroline da Silva; Mesquita, Rafael D.; Dillon, Viv M.; Garcia, Eloi de Souza; Azambuja, Patricia; Dillon, Roderick J.; Genta, Fernando A. (Frontiers in Physiology, 2017)
Triatominae is a subfamily of the order Hemiptera whose species are able to feed in the vertebrate blood (i.e., hematophagy). This feeding behavior presents a great physiological challenge to insects, especially in Hemipteran species with a digestion performed by lysosomal-like cathepsins instead of the more common trypsin-like enzymes. With the aim of having a deeper understanding of protease involvement in the evolutionary adaptation for hematophagy in Hemipterans, we screened peptidases in the Rhodnius prolixus genome and characterized them using common blast (NCBI) and conserved domain analyses (HMMER/blast manager software, FAT, plus PFAM database). We compared the results with available sequences from other hemipteran species and with 18 arthropod genomes present in the MEROPS database. Rhodnius prolixus contains at least 433 protease coding genes, belonging to 71 protease families. Eight peptidase families in R. prolixus presented higher gene numbers when compared to other arthropod genomes. Further analysis indicated that a gene expansion of the protease family A1 (Eukaryotic aspartyl protease, PF00026) might have played a major role in the adaptation to hematophagy since most of these peptidase genes seem to be recently acquired, are expressed in the gut and present putative secretory pathway signal peptides. Besides that, most R. prolixus A1 peptidases showed high frequencies of basic residues at the protein surface, a typical structural signature of Cathepsin D-like proteins. Other peptidase families expanded in R. prolixus (i.e., C2 and M17) also presented significant differences between hematophagous (higher number of peptidases) and non-hematophagous species. This study also provides evidence for gene acquisition from microorganisms in some peptidase families in R. prolixus: 1) family M74 (murein endopeptidase), 2) family S29 (Hepatitis C virus NS3 protease), and 3) family S24 (repressor LexA). This study revealed new targets for studying the adaptation of these insects for digestion of blood meals and their competence as vectors of Chagas disease.